2001
DOI: 10.1034/j.1600-0501.2001.120603.x
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Width around one‐ and two‐piece titanium implants

Abstract: Gingival esthetics around natural teeth is based upon a constant vertical dimension of healthy periodontal soft tissues, the Biologic Width. When placing endosseous implants, however, several factors influence periimplant soft and crestal hard tissue reactions, which are not well understood as of today. Therefore, the purpose of this study was to histometrically examine periimplant soft tissue dimensions dependent on varying locations of a rough/smooth implant border in one-piece implants or a microgap (interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
167
2
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(191 citation statements)
references
References 26 publications
7
167
2
15
Order By: Relevance
“…MBL values reported in this study were lower compared to other studies with similar observation periods (Boronat et al, 2008;Collaert and De Bruyn, 2008;Testori et al, 2008;Tözüm et al, 2008;Bergkvist et al, 2009;Piao et al, 2009;Song et al, 2009). Bone loss for healed sites (group I) in our study was about 0.266 ± 0.176 mm while with another study it showed an increase of up to 0.78 mm (Ericsson et al, 2000), which can be explained by the formation of the biological width (Hermann et al, 2001). In another reports, with the same implant systems, the mean value of MBL was 0.40 ± 1.43 mm (Cooper et al, 2010) and 0.40 ± 1.51 mm (De Bruyn et al, 2013) for a 3 years observation period.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…MBL values reported in this study were lower compared to other studies with similar observation periods (Boronat et al, 2008;Collaert and De Bruyn, 2008;Testori et al, 2008;Tözüm et al, 2008;Bergkvist et al, 2009;Piao et al, 2009;Song et al, 2009). Bone loss for healed sites (group I) in our study was about 0.266 ± 0.176 mm while with another study it showed an increase of up to 0.78 mm (Ericsson et al, 2000), which can be explained by the formation of the biological width (Hermann et al, 2001). In another reports, with the same implant systems, the mean value of MBL was 0.40 ± 1.43 mm (Cooper et al, 2010) and 0.40 ± 1.51 mm (De Bruyn et al, 2013) for a 3 years observation period.…”
Section: Discussionmentioning
confidence: 67%
“…The microgap between implant-abutment and disruption of the soft tissue that occurs each time the two are disconnected and reconnected, are thought to influence bone resorption around implant neck. Some amount of bone resorption occurs during the first year of loading (Hermann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In an overly coronal situation there will be the esthetic risk of the the exposure of the abutmentimplant interface. Conversely, an overly apical positioning will create an unstable periodontal environment because it will create a sulcus more than 4 mm deep, making it a potential periodontal pocket 10,12 . The proper location for the osseous crest should be no more than 4 to 5 mm from a line passing through the gingival border around the replacement tooth the way it would have with the contra-lateral tooth.…”
Section: Figure 23mentioning
confidence: 99%
“…Two designs are currently in use, one with a supracrestal neck, the other with neck at the level of the crest. The first will have a neck that is located 1.5 mm apical to the line of the cementoenamel junction 1,12 . The design of implants that lie at the crest will have necks 3 to 4 mm apical to the line of the cemento-enamel junction 7,9,10,14,16 .…”
Section: Figure 23mentioning
confidence: 99%
“…A estabilidade primária é essencial na Implantodontia Odontológica para que ocorra a cicatrização natural e formação óssea efetiva (Morton et al, 2004;Chong et al, 2009), assim como para a manutenção de tecidos duros e moles periimplantares (Hermann et al, 2001;Glauser et al, 2004;Salmória et al, 2008); portanto, é uma condição determinante para a ocorrência da osseointegração Carvalho et al, 2008, Cehreli et al, 2009a, 2009bChong et al, 2009;Browers et al, 2009;Kahraman et al, 2009;Degidi et al, 2010).…”
Section: Introductionunclassified